Numerical Solution for Reversible Chemical Reaction Models with Interactive Fuzzy Initial Conditions - Wasques, Vinicius F. [UNESP]; Esmi, Estevao; Barros, Laecio Carvalho de; Santo Pedro, Francielle; Bede, B.; Ceberio, M.; DeCock, M.; Kreinovich, V (Springer, 2022)
This manuscript studies the reversible chemical reactions described by a system of fuzzy differential equations, with initial conditions given by interactive fuzzy numbers. The fuzzy solution is given by the Euler method based on the arithmetic for interactive fuzzy numbers. An example is presented in order to illustrate the different types of interactivity that produce the solutions for the system.
Keywords: Fuzzy initial value problem; Sup-extension principle; Interactive fuzzy numbers; Chemical reactions